Impact of cultivar selection on floral hemp yield and cannabinoid production in the semiarid Intermountain West - Tina Sullivan; Matt Yost; Dakota Boren; Earl Creech; Bruce Bugbee (Agrosystems, Geosciences & Environment)
Abstract Hemp (Cannabis sativa L.) cultivar development rapidly progressed with floral hemp production legal in many US states following the 2018 Farm Bill. Desirable floral hemp cultivar traits include high biomass, high cannabidiol (CBD), cannabigerol (CBG), and other cannabinoids, and, most importantly, legally compliant Δ9‐tetrahydrocannabinol (THC) levels that avert crop destruction. As a reemerging crop, limited cultivar trials have been conducted recently in the United States. Further, improved understanding of floral initiation photoperiods and performance of various cultivars under commonly used overhead irrigation is needed. Field performance trials were conducted in 2020–2022 near Logan, UT, to test common regionally available cultivars and to determine floral initiation and subsequent harvest maturities. Available cultivars were different each year in a rapidly evolving market, but many cultivars were tested for multiple seasons. High variation and changes in cannabinoid concentrations near harvest provided evidence that early floral detection and harvest timing are critical for THC compliance. Early cultivars (15 h initiation) produced more floral compared to leaf biomass than those that flowered later. Later flower cultivars often produced statistically similar biomass weight among cultivars, but more leaf material compared to floral, evident with lower amounts of CBD and THC. The greatest CBD‐yielding cultivars at legal THC limits were Berry Blossom, Dutch Delight, and Trump with 10%–17% of all tested cultivars over the limit across the site‐years. However, high variability in performance and ranking of cultivars indicates that longer term testing may be required to select the most ideal cultivars for each region.